Study on supercapacitors - Abdullah Omar Salleh (2011)
Supercapacitors have excellent power density (kW/kg) and good energy density (Wh/kg) many orders of magnitude in comparison to conventional capacitors. They present much promise in energy storage for electrical and electronic applications with their long lifetime, quick charge and discharge time and with no maintenance as compared to batteries. As the study of supercapacitor is in the infancy stage, this study focuses on compilation of various researches available that are up to date. This serves to create the base structure of the study so that eventually, an accurate electrical simulation model may be created to study its electrical and electronic performances in applications. The study covers the physical structure of the supercapacitor, electrical characterization, voltage balancing techniques and applications that benefit from the supercapacitor’s unique characteristics. This study uncovers several areas of improvement on the field of supercapacitors such as electrical characterization and voltage balancing. The study concludes and supports the enormous potential of supercapacitors in the future demands on power engineering in cost savings as well as energy efficiency.